Jan Cep on Radio Free Europe - Kopecka-Valeska, Olga (Bohemica Olomucensia, 2015)
The article presents memories of Cep's listener and later colleague who after Cep's death became the editor of his texts written for the Radio Free Europe broadcast.
Keywords: Jan Cep; Radio Free Europe; memories; broadcast essays